2014
DOI: 10.1002/gcc.22141
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent mutation of JAK3 in T‐cell prolymphocytic leukemia

Abstract: T-cell prolymphocytic leukemia (T-PLL) is an aggressive post-thymic T-cell malignancy characterized by the recurrent inv(14)(q11q32)/t(14;14)(q11;q32) or t(X;14)(q28;q11) leading to activation of either the TCL1 or MTCP1 gene, respectively. However, these primary genetic events are insufficient to drive leukemogenesis. Recently, activating mutations in JAK3 have been identified in other T-cell malignancies. Since JAK3 is essential for T-cell maturation, we analyzed a cohort of 32 T-PLL patients for mutational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 42 publications
7
51
0
Order By: Relevance
“…3,4,[8][9][10] Thus, it has been shown that JAK pseudokinase domains are auto-inhibitory and keep the kinase domain inactive until receptor dimerization stimulates transition to an active state. 11 Molecular analysis of deregulated JAK/STAT signaling has provided a novel rationale for treating human cancers using targeted inhibition of JAK kinases.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…3,4,[8][9][10] Thus, it has been shown that JAK pseudokinase domains are auto-inhibitory and keep the kinase domain inactive until receptor dimerization stimulates transition to an active state. 11 Molecular analysis of deregulated JAK/STAT signaling has provided a novel rationale for treating human cancers using targeted inhibition of JAK kinases.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…1 Sequencing studies have identified recurrent mutations in both JAK1 and JAK3 in several hematological malignancies. [2][3][4][5][6][7][8][9][10] We described the importance of JAK3 mutations in the development of T-cell acute lymphoblastic leukemia (T-ALL) and showed that a majority of JAK3 mutants require both binding to the common g chain and presence of JAK1 for their transforming capacities. [11][12][13] However, the JAK3 L857Q/P and L875H kinase domain mutants are exceptions and do not require the common g chain or JAK1 for their transforming capacity.…”
Section: Introductionmentioning
confidence: 99%
“…67 With regards to malignancies of lymphoid lineage, JAK3 mutations were reported in a significant proportion of T-ALL, 68 especially in an aggressive subtype called early T-cell precursor-ALL, 38 as well as in diverse mature Tcell neoplasms. 40,42,[69][70][71] More recently, TYK2 mutants were discovered in T-ALL (21%) and seem to promote cell survival via activation of STAT1 downstream of IL-10R and upregulation of the anti-apoptotic BCL2 protein. …”
mentioning
confidence: 99%